The Effects of Cold Exposure and Energy Deficit on Energy Balance - McInnis, Kurt Michael (Université d'Ottawa | University of Ottawa, 2025)
The main objective of this thesis was to examine the effects of cold exposure (CE) on energy intake (EI), energy expenditure (EE), hunger, and body weight in individuals living with obesity and determine its feasibility as a weight loss tool. The first article reviewed the current state of the literature, highlighted the gaps in knowledge surrounding individuals living with obesity and EI in CE research, and identified the research questions to be addressed. The second article examined the effects of acute CE on energy balance, hunger, and thermoregulatory outcomes. CE caused both EI and EE to increase, but the magnitude of both changes was quite small while having no impact of appetite. Skin temperature, peptides, thermal comfort and thermal sensation all demonstrated that the CE stimulus was potent, but EE only increased by an average of 20.3±20.6 kcal over 90 minutes, a mere 12% of what lean individuals undergoing the same stimulus would experience. The third article examined the effects of three 8-week weight loss interventions on energy balance, body weight and appetite: a dietary restriction of 30% (DIET), 28 cold sessions (CE), or both stimuli together (DIET+CE). CE alone did not result in weight loss or significantly improve weight loss outcomes when combined with a dietary restriction. EE increased for all three groups post intervention, thermal sensation improved post intervention for all groups, and subjective appetite changed between the three groups. EI and skin temperature did not change significantly post intervention. For the first time, CE was shown to not significantly improve weight loss outcomes alone or when used in combination with a dietary restriction. High levels of thermal discomfort, minimal increases in heat production during CE, and high dropout rates highlight the challenges in feasibility of using CE as a weight loss adjunct.
Keywords: Obesity; Weight loss; Cold Exposure; Thermoregulation